Investigation of a commercial lithium-ion battery under overcharge/over-discharge failure conditions. Issue 58 (27th September 2018) - Ouyang, Dongxu; Chen, Mingyi; Liu, Jiahao; Wei, Ruichao; Weng, Jingwen; Wang, Jian
Abstract : A lithium-ion battery (LIB) may experience overcharge or over-discharge when it is used in a battery pack because of capacity variation of different batteries in the pack and the difficulty of maintaining identical state of charge (SOC) of every single battery. Abstract : A lithium-ion battery (LIB) may experience overcharge or over-discharge when it is used in a battery pack because of capacity variation of different batteries in the pack and the difficulty of maintaining identical state of charge (SOC) of every single battery. A series of experiments were established to investigate the thermal and fire characteristics of a commercial LIB under overcharge/over-discharge failure conditions. According to the results, it is clear that the batteries experienced a clear temperature rise in the overcharge/over-discharge process. The temperature rise worsened and required less time when the battery was overcharged/over-discharged to failure with the increasing charge/discharge rate. Besides, the closer the position to the opening of the battery, the higher the surface temperature. It was demonstrated that LIBs can fail when overcharged/over-discharged to a critical degree regardless of the charge/discharge rate. Under different rates, the final capacities were around a critical value. Finally, there existed an explosion phenomenon in the external heating test of battery failure after overcharge, whereas the fire behaviors of the over-discharged battery were much more moderate.